Inexpensive and green synthesis of multi-doped LiFePO4/C composites for lithium-ion batteries. (10th December 2017) - Liu, Wanmin; Liu, Qilong; Qin, Mulan; Xu, Lv; Deng, Jiyong
Abstract: Multi-doped LiFePO4 /C has been successfully synthesized using iron powder as an iron source and spent electroless nickel plating solution (SENPS) as phosphorus, carbon and dopants sources. A possible liquid-phase and solid-phase mechanisms for the formation of multi-doped LiFePO4 /C are also proposed. The structure, morphology, elemental composition and particle size distribution of the powder are characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy and laser particle size analyzer, respectively. The charge-discharge tests demonstrate that the electrochemical properties of the material are comparable to that of the similar material prepared from SENPS and ferric oxide or ferrous oxalate, with the initial discharge capacities of 165.1, 158.8, 152, 145.8, 133.1 and 120.2 mAhg −1 at 0.1, 0.5, 1, 2, 5 and 10 C, respectively, and excellent cycling performance at 1 C .